“Ireland of the East”? A Case of the Anticolonial Rhetoric in the Ukrainian National Movement (1870s–1923) - Gennadii Korolov (Zeitschrift für Ostmitteleuropa-Forschung)
The article examines the emergence and use of the Irish example in the political rhetoric of the Ukrainian national movement. The author traces how prominent Ukrainian politicians and intellectuals understood and used the ideas of the Irish national liberation movement. Special attention is paid to the period from 1917 to 1923 when leaders used the Irish example in political and ideological arguments to illustrate Ukraine’s colonial status within the Russian Empire. The use of the Irish example is presented in the context of forming an argument about this colonial status, as well as the justice of their national struggle and demands for national and economic liberation. The author also emphasizes that the anticolonial rhetoric of the Ukrainian national movement was not explicit enough. Therefore, the reference to Ireland was an attempt to find a similar example of a national struggle against imperial domination. In addition, the Irish language example was identified with the status and development of the Ukrainian language as part of a resistance to assimilation policies and imperial restrictions on language and culture.